Downregulation of Cancer-Associated lncRNAs in Peripheral Blood of Multiple Sclerosis Patients - Safa, Amin; Taheri, Mohammad; Fallah, Hamid; Salmani, Tayyebali; Arsang-Jang, Shahram; Ghafouri-Fard, Soudeh; Omrani, Mir Davood (Journal of molecular neuroscience, 2020)
Recent studies have shown contribution of long non-coding RNAs (lncRNAs) in the pathogenesis of immune-related disorders including multiple sclerosis (MS). Based on the role of these transcripts in the regulation of immune response, peripheral levels of lncRNAs can reflect the level of immune activation. In the present study, we quantified expression of four lncRNAs namely SPRY4-IT1 , HOXA-AS2 , LINC-ROR , and MEG3 in venous blood of MS patients and controls using quantitative real-time PCR method. Relative expressions of SPRY4-IT1 , HOXA-AS2 , LINC-ROR , and MEG3 were significantly lower in female MS patients compared with female healthy subjects. For MEG3 , this pattern of expression was also observed in male subjects. However, for other lncRNAs, no significant difference was detected between male patients and male controls. Expression of HOXA-AS2 was correlated with progression index ( r = 0.36, P < 0.001). Besides, there was a significant correlation between expression of this lncRNA and expression of LINC-ROR in MS patients ( r = 0.44, P < 0.0001). There was no other correlation between expression of lncRNAs and clinical data in MS patients. In control group, expressions of none of lncRNAs were correlated with age of persons. Notably, significant correlations were demonstrated between expression levels of all lncRNAs in healthy subjects with r values ranging from 0.23 to 0.42. The current investigation shows dysregulation of lncRNAs in MS patients in a sex-specific manner and warrants further studies to unravel the clinical and therapeutic implications of such dysregulation.